Dos cursos da vida e das vidas em curso: práticas de medicalização da infância e suas relações com currículos de profissionais de saúde em um CAPSi em Belém do Pará - SANTOS, Daniele Vasco (Universidade Federal do Pará, 2017)
The following research was raised from medicalization practices focused on childhood care in a mental health service and its relationship with the health professional‟s curricula. Intensive medicalization has increasingly improved strategies that employ expert- oriented clinical practices and diagnosis concerning social deviations, based on pathologizing, psychologizing and biomedical rationalities. Brazilian public policies are among these children and adolescent‟s mental health practices at Children and Youth Psychosocial Care Center - CAPSI, which have been officially established since 2001, under the law number 10.216 that converts health care to population that suffers mental disorder. This research object was shaped by coupling medicalization practices with subjectivation/objectification modes of children and the discourses produced on health professional curricula. This study started at the point it was realized the professional‟s performance were based on some curricula, and from its analysis it is also possible to understand the processes by which certain settings that intend to frame subjects. Thus, in order to enhance this thesis, it was employed these issues: How can subjectivation/ objectification modes find mental disorders in children at CAPSI? To what extent do the discourses which support medicalization practices at CAPSI correspond to the curricula of professionals working in these places? In order to look into medicalization practices at CAPSI and their relationship with the curricula of health professionals, the following purposes were developed: To analyze subjectivation/objectification modes whereby such children are diagnosed as "mentally disabled"; investigate medicalization discourses given by professionals who care children with “mental disorder”. It was used as theoretical and methodological framework Michel Foucault‟s theory of power-knowledge, biopolitics, governableness, among other scholars such as Veyne (1998), Silva (2006), Veiga-Neto (2003), Corazza; Aries; Robert Castel, Jacques Donzelot. Main analysed documents were the medical records registered at CAPSI and interviews with professionals by using general principles of archaeological procedures as methodological tools of historical-documentary research. Therefore, it was asserted with this thesis that the modes of subjectivation and objectification which yield children with "mental disorders" are constituted through a close relationship with medicalizing discourses which have been given in the curricula of health professionals in their official education, daily service routine and in different fields of life.